Doing fieldwork in areas of international intervention : a guide to research in violent and closed contexts - Bliesemann de Guevara, Berit; Bøås, Morten, 1965- (Spaces of peace, security and development., 2020)
Using insights from those with first-hand experience of conducting research in areas of international intervention and conflict across the world, this book provides essential practical guidance, discussion of mistakes, key reflections and raises important questions for researchers and students embarking on fieldwork in violent and closed contexts.